University politics in the framework Of the Gran Acuerdo Nacional (1971-1973) (Estudios Sociales, 2018)
The period that began with Lanusse in May 1971 determined a turning point in national politics and, consequently, in university life. In this article, we aim to analyze the creation of new national universities that took place between 1971 and 1973 within the framework of the Gran Acuerdo Nacional. We will emphasize on the context of a strong process of political radicalization in which youth was very important. For this, we will use primary and secondary sources. Specifically we will resort to personal interviews, national newspapers, and official university documents (development plans, laws, educational policies, among others).
Keywords: Gran Acuerdo Nacional; University policies; Universities; Youth